2018
DOI: 10.7759/cureus.3773
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Written Assessment Methods: Multiple-choice and Short Answer Questions in End-of-clerkship Examinations for Final Year Medical Students

Abstract: Introduction An important aspect of a modern academic curriculum is assessment, which can be clinical and written. Written assessment includes both multiple-choice questions (MCQs) and short answer questions (SAQs). Debate continues as to which is more reliable. It is important to assess the correlation between the two different formats of written assessments, especially in the clinical subjects as they are different from the basic science subjects. Moreover, data are lacking in the correlation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 17 publications
(40 reference statements)
0
20
0
Order By: Relevance
“…5 Study by Mahmood (2015) shows moderate correlation between the MCQs and SEQS, however inter-rater reliability of SEQs showed high correlation. 8 Similar study was done by Farooqui et al 9 to assess the correlation of MCQs and SEQs in medicine, surgery, pediatrics and obstetrics and gynecology examinations. Moderate positive significant correlation was found between MCQs and SEQs in three subjects except for obstetrics and gynecology where weak positive correlation was found.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…5 Study by Mahmood (2015) shows moderate correlation between the MCQs and SEQS, however inter-rater reliability of SEQs showed high correlation. 8 Similar study was done by Farooqui et al 9 to assess the correlation of MCQs and SEQs in medicine, surgery, pediatrics and obstetrics and gynecology examinations. Moderate positive significant correlation was found between MCQs and SEQs in three subjects except for obstetrics and gynecology where weak positive correlation was found.…”
Section: Introductionmentioning
confidence: 82%
“…Author suggested that additional studies are needed to determine the correlation between these two modes of examination and increase the validity of assessments via SEQ's. 9 Moderate positive correlation (r = 0.5 P < 0.01) between scores of MCQs and SEQs was found in the send up undergraduate examination for Ophthalmology. 8 On the other hand astudy showed significant positive correlation of performance between SEQs with MCQs in the subject of Pharmacology at Kasturba Medical College at Manipal University, Karnataka, India.…”
Section: Performance Of Students In Seqs and Mcqs Inmentioning
confidence: 89%
“…A study showed that more students had scores greater than the median in the SAQs scores (14). Another study found that a statistically significant overall correlation between students' performance on MCQs and SAQs in major clinical subjects (9).…”
Section: Resultsmentioning
confidence: 99%
“…In SAQs marking, there is a wider standard deviation by bias or variable marking by different examiners whereas marking is more consistent in MCQs (9). However, SAQs have high validity as students need to be able to generate the piece of knowledge in the absence of cues, an approach that is more representative of real-life medical practice (5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation